1987
DOI: 10.1007/bf00275743
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow irradiation chimeras in the BB rat: evidence suggesting two defects leading to diabetes and lymphopoenia

Abstract: Summary. A series of bone marrow irradiation chimeras were constructed in an attempt to determine the site of the defect(s) leading to diabetes and/or lymphopoenia in the BB rat. In BB rats that were lethally irradiated and reconstituted with T-cell-depleted Wistar-Furth (WF) rat bone marrow, the incidence of diabetes was reduced, and in animals treated with WF bone marrow at < 44 days of age, the disease was completely prevented. Such animals demonstrated normal lymphocyte counts in peripheral blood, and norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…as previously described. 7 - 8 Individual rats were classified as diabetic on the basis of positive, sustained glycosuria as described previously. 78 Each diabetic rat was subsequently maintained on a single daily dose of PZI insulin (Eli Lilly and Co., Indianapolis, Ind.…”
Section: -2mentioning
confidence: 99%
“…as previously described. 7 - 8 Individual rats were classified as diabetic on the basis of positive, sustained glycosuria as described previously. 78 Each diabetic rat was subsequently maintained on a single daily dose of PZI insulin (Eli Lilly and Co., Indianapolis, Ind.…”
Section: -2mentioning
confidence: 99%
“…2A and C, respectively. normal lymphocyte counts in peripheral blood, normal lymphocyte function, and normal T cell subset distributions [18]. The recipient WF rats transplanted with BBDP T cell-depleted bone marrow cells did not differ from control WF to WF rats and WF to BB rats, suggesting that both a lymphoid stem cell as well as differentiating environment influenced the lymphopenia phenotype and diabetes [30].…”
Section: Discussionmentioning
confidence: 96%
“…The same authors suggested from bone marrow transplantation experiments between RT1 B u/u compatible BB and WistareFurth rats that there were two defects leading to lymphopenia and diabetes. One of these would occur in the bone marrow stem cells while the other resides in the T cell differentiating environment since lethally irradiated WistareFurth recipient rats did not develop lymphopenia or diabetes when receiving bone marrow cells from diabetic BB rats [18]. Other investigators suggested that bone marrow stem cells [19,20] or a combination of thymic and bone marrow defects [21] were responsible for the altered immune state of the bone marrow recipient rat.…”
Section: Introductionmentioning
confidence: 98%